(3GdCcSLjf djS ddehJi(B/s - (3CHh fOi; gHIs; Abou Nada, Heba ((3GdchjJ;s (3OGQ OjhGf;s, 2021)
The story follows the protagonist's relationship with an intelligence officer named Adam, delving into his emotional struggles and second marriage following the suicide of his first wife. The narrative is conveyed through the perspective of the protagonist, the son of a Minister of Interior targeted for assassination.
(3hEPG cGf dbGQF (B"(3GdCcSLjf djS ddehJi(B" (3Gf jCoNnP YdjgG GSJQSGdG aj ZjQ ehVmY, heUGOaGmJ aj hbGFY eJJGHYmI djSJ oebfYkI ZGdHG, EdG Cf gPjf GdCeQrjf (B((3hZjQgeG QHeG(B) (3dG jfajGf HQGYI pgHI CHh fOi aj YHhQgG GdLqhGfj aj TNUqjGJgG, haj eZGeQJgG GdNGqUI YfOeG JfTZd HVGHW eNGHQGJ (B((3GSoeg BOe(B) (3hOhGpNdg, hbdpbg, hGVWQGHGJg GdfaSjI, heSGAdGpJg fanSg, hJMqhdGmJ aj MTGjGg, heMqHI RhLJg dg, hgj GdJj GbJQnf HgG HYO TaGFg GdfSHj eeG UGQ Ydjg MGodg YbH GfJMGQ YQhpSg GdChdi aj jhe RhGpLgeG, hoJHfi GdQhGjI HVejpQg GdeJcqde (B((3HGSJKfGA eSGMGmJ bdjdmI dZjpQg(B)(3, hgh fLd hRjmQ ddOGNdjI jbVj GZJjGdGs
Title translation: Oxygen is not for the dead- Heba Abu Nada
Arabic
Keywords: Contemporary (1990 onwards); Fiction; PJ7501-8517 Arabic literature; Kuwait